The Role of Environmental Fiqh in Tackling the Problem of Non-Organic Waste in Yogyakarta's Tourist Areas - Hanip Al Hadid; M. Roem Syibly (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
The waste problem in Yogyakarta has become a pressing environmental issue, especially amidst increasing urbanization and population growth. The closure of the Piyungan landfill, which was expected to be a long-term solution, has instead created new challenges in waste management. This study explores the implementation of environmental fiqh concepts in waste management in Yogyakarta as an effort to align pro-environmental actions with Islamic values. This study employed library research with a normative approach, using secondary data sources, and qualitative descriptive analysis. The analysis focused on waste issues, regulations, and environmental jurisprudence (fiqh). The results indicate that Yogyakarta's waste problem, exacerbated by population growth and urbanization, represents a pressing environmental challenge. Although the government has taken steps such as the closure of the Piyungan landfill and the decentralization of waste management, challenges such as the lack of recycling facilities and low public awareness remain major obstacles. Regulations such as Law No. 18 of 2008 and Regional Regulation No. 1 of 2022, although important, have not been optimally implemented.